Rare copy number variants in a population‐based investigation of hypoplastic right heart syndrome. Issue 1 (20th January 2017) - Dimopoulos, Aggeliki; Sicko, Robert J.; Kay, Denise M.; Rigler, Shannon L.; Druschel, Charlotte M.; Caggana, Michele; Browne, Marilyn L.; Fan, Ruzong; Romitti, Paul A.; Brody, Lawrence C.; Mills, James L.
Abstract : Background: Hypoplastic right heart syndrome (HRHS) is a rare congenital defect characterized by underdevelopment of the right heart structures commonly accompanied by an atrial septal defect. Familial HRHS reports suggest genetic factor involvement. We examined the role of copy number variants (CNVs) in HRHS. Methods: We genotyped 32 HRHS cases identified from all New York State live births (1998–2005) using Illumina HumanOmni2.5 microarrays. CNVs were called with PennCNV and prioritized if they were ≥20 Kb, contained ≥10 SNPs and had minimal overlap with CNVs from in‐house controls, the Database of Genomic Variants, HapMap3, and Childrens Hospital of Philadelphia database. Results: We identified 28 CNVs in 17 cases; several encompassed genes important for right heart development. One case had a 2p16‐2p23 duplication spanning LBH, a limb and heart development transcription factor. Lbh mis‐expression results in right ventricular hypoplasia and pulmonary valve defects. This duplication also encompassed SOS1, a factor associated with pulmonary valve stenosis in Noonan syndrome. Sos1 −/− mice display thin and poorly trabeculated ventricles. In another case, we identified a 1.5 Mb deletion associated with Williams‐Beuren syndrome, a disorder that includes valvular malformations. A third case had a 24 Kb deletion upstream of the TGFβ ligand ITGB8 . Embryos genetically null for Itgb8, and its intracellular interactant Band 4.1B, display lethal cardiac phenotypes. Conclusion: To our knowledge, this is the first study of CNVs in HRHS. We identified several rare CNVs that overlap genes related to right ventricular wall and valve development, suggesting that genetics plays a role in HRHS and providing clues for further investigation. Birth Defects Research 109:16–26, 2017. © 2016 Wiley Periodicals, Inc.